SARS-CoV-2-related Multisystem Inflammatory Syndrome in Children: A case series - Al Maskari, Nawal (Sultan Qaboos Univ Med J, 2021)
On 27 April 2020, the National Health Service England issued an emergency alert for a new condition owing to the observation of an increasing number of cases of a COVID-19-related hyperinflammatory syndrome termed multisystem inflammatory syndrome in children (MIS-C). Some of the presenting symptoms appeared similar to the Kawasaki disease and toxic shock syndrome. We report the cases of six children fitting the criteria of MIS-C, admitted to Royal Hospital and Sohar Hospital, Oman, between the months of June and July in 2020. Four of these patients required admission at the paediatric intensive care unit for inotropic support while two were admitted to the paediatric ward on suspicion of appendicitis. MIS-C has been reported in a small number of individuals below the age of 21 years with a median age of 9–10 years. Five of the current patients were aged less than the median age reported in the existing literature. All of the patients showed complete recovery with supportive management, intravenous immunoglobulin and steroids, with one patient requiring interleukin-6 inhibitor (tocilizumab).